ACOUSTIC EMISSION IN QUARTZITE OF KRYVYI RIG OVER DEEP BOREHOLE - BEZRODNYI, D.; LIASHENKO, O.; VELESHCHUK, V.; ONANKO, A.; ONANKO, Yu. (Visnyk of Taras Shevchenko National University of Kyiv. Geology, 2024)
Effects of acoustic emission under thermal-mechanical strains in quartzite are investigated. Elastic waves pulses are discovered from micro fractures that of probably connected with elastic balance in quartzite.